Estudo da adição de resíduo de scheelita em matriz cerâmica: formulação, propriedades físicas e microestrutura - Machado, Tercio Graciano (2012)
Extractivism mineral is considered an activity highly degrading, due to the large volume of material that he moves in the form of ore and residues. The vast majority of mining companies do not show any technology or economically viable application that will allow the recycling of mineral residue, these being launched in areas receiving located the "open skies" degrade the environment. In Rio Grande do Norte to the production of ceramic red restricts their activities to the production of products such as: solid bricks, ceramic blocks, tiles, among others. Seeking to unite experiences and technical information that favor sustainable development, with important benefits to the construction sector and civil society in general, the present work studies the incorporation of the residue of scheelite in ceramic matrix kaolinitic, coming from the municipality of Boa Saúde - RN, in percentage of 5 %, 10 %, 20 %, 30% 40% and 50 %, by evaluating its microstructure, physical properties and formulation. The raw materials were characterized through the trials of X ray fluorescence, Diffraction of X rays, Differential Thermal Analysis and Termogravimetric Analysis. The samples were formed and fired at temperatures of 850o, 900o, 1000o, 1050o, 1100o, 1150o and 1200 oC, with isotherm of 1 hour and heating rate of 10 oC/min. Assays were performed technological of loss to fire, Water Absorption, Apparent Porosity, Apparent Density, Mass Loss in Fire and Bending Resistance; in addition to the Scanning Electron Microscopy, analyzing their physical and mechanical properties. The use of residue of scheelite in ceramic mass kaolinitic provided a final product with technological properties that meet the technical standards for the production of bricks and roofing tiles, with the percentage of 20% of waste that showed the best results